Well-being, greenery, and active mobility: Urban design proposals for a network of proximity hubs along the new M4 metro line in Milan - Fior, Marika; Galuzzi, Paolo; Vitillo, Piergiorgio (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The paper summarizes the results obtained from the action research conducted at Politecnico di Milano (2018-2020) for Milan Municipality and MM4 SpA. It is a Masterplan for reorganizing areas and public spaces along the new M4 metro line route. The paper aims to highlight the positive effects that planning at various scales brings to the city in terms of new green areas, new spaces for inhabitants and users, and new routes to get around the city. The three concerns are at the basis of a conscious process of improvement of living conditions in the major urban areas worldwide, which are increasingly characterized not only by climate, environmental and social inclusion problems but also by health problems. Without disturbing the pandemic issue, important urban matters must be addressed from an urban health perspective to support the prevention of chronic degenerative diseases. Policies for the re-greening of the city and the extension of slow mobility routes help in this task. The paper shows how these strategic actions can be adapted to the dense and stratified fabric of Milan city to achieve and boost a model of a healthy, active, and sustainable city.